2023
DOI: 10.2147/dmso.s408075
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Glucose Index is Significantly Associated with the Risk of Hyperuricemia in Patients with Nonalcoholic Fatty Liver Disease

Abstract: The triglyceride-glucose (TyG) index is a new index of insulin resistance (IR), and its association with hyperuricemia (HUA) is unclear. The aim of this study was to investigate whether TyG is an independent risk factor for hyperuricemia (HUA) in patients with nonalcoholic fatty liver disease (NAFLD). Patients and Methods: We retrospectively analyzed 461 patients with ultrasound-confirmed NAFLD and calculated the TyG index. Multivariate logistic regression was used to analyze the relationship between the TyG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Qi et al revealed that TyG index could be considered as a risk factor for developing hyperuricemia among patients in nonalcoholic fatty liver disease (NAFLD) [37].…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al revealed that TyG index could be considered as a risk factor for developing hyperuricemia among patients in nonalcoholic fatty liver disease (NAFLD) [37].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]. Several studies have reported an association between the TyG index and hyperuricemia [9][10][11] suggesting that the TyG index may also be related to gout.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have investigated the association between the TyG index and hyperuricemia in different populations. A retrospective case-control study found that the TyG index was an independent risk factor for hyperuricemia in patients with non-alcoholic fatty liver disease (NAFLD) (OR[95 %CI]:2.00[1.38,2.91]) ( Qi et al, 2023 ). In addition, in a longitudinal study, the TyG index was also positively correlated in diabetic kidney disease (DKD) adults [15].…”
Section: Introductionmentioning
confidence: 99%